A method for the separation and reconstructions of charged hadron and neutral hadron from their overlapped showers in an electromagnetic calorimeter - 梁松 陶军全 沈玉乔 范嘉伟 肖虹 陈国明 陈和生 卞建国 陈晔 李祖豪 孟祥伟 唐志成 汪先友 王征 徐明 许伟伟 严琪 杨民 张诚 朱世海 (Chinese physics C, 2013)
The separation and reconstructions of charged hadron and neutral hadron from their overlapped showers in an electromagnetic calorimeter is very important for the reconstructions of some particles with hadronic decays, for example the tau reconstruction in the searches for the Standard Model and supersymmetric Higgs bosons at the LHC. In this paper, a method combining the shower cluster in an electromagnetic calorimeter and the parametric formula for hadron showers, was developed to separate the overlapped showers between charged hadron and neutral hadron. Taking the hadronic decay containing one charged pion and one neutral pion in the final status of tau for example, satisfied results of the separation of the overlapped showers, the reconstructions of the energy and positions of the hadrons were obtained. An improved result for the tau reconstruction with this decay model can be also achieved after the application of the proposed method.